Teknik Pengelolaan Media Sosial @demarapictures untuk Menarik Minat Konsumen - Muhammad Aldi Satria Pratama; Noning Verawati; M Denu Poyo (Penerbit Jurnal Indonesia, 2025)
This study aims to understand the social media management techniques used by @demarapictures to attract consumer interest in the digital era. The research method employed is descriptive qualitative with a case study approach focusing on promotional activities and digital communication through the Instagram platform. Data were collected through in-depth interviews with photographers and editors involved in content management, direct observation of the photo and video production and editing processes, as well as documentation of internal communication in the form of digital messages and work notes. The data were analyzed thematically to identify patterns, techniques, and challenges encountered in building audience engagement. The expected results of this study are aligned with its objectives, namely to identify and analyze the social media management techniques applied by the @demarapictures account to attract consumer interest. This research is expected to uncover content techniques, types of media used, posting frequency, and effective ways of interacting with followers to increase engagement, followers, and consumer purchase interest. In addition, the study aims to determine the most influential techniques in capturing consumer attention and to provide recommendations for optimal social media management so that @demarapictures can maximize the potential of social media as a promotional and communication tool with its target market.